Effectiveness Of Electronically Integrated Business Perizances Through Online Single Submission (OSS) In Bogor District - Nugraha, Adhi; Adiwijaya , Achmad Jaka Santos; Nuradi (Universitas Djuanda, 2024)
The government was trying to create an optimal service system to meet the needs of the community in managing permits, namely by implementing OSS. This system was built by implementing electronically integrated business licensing and enhanced by the implementation of the OSS Risk Based Approach (RBA) in 2021. The purpose of this study was to determine and analyze the effectiveness of electronically integrated business licensing through Online Single Submission ( OSS ) in Bogor Regency. This research used sociological juridical research methods, with data collection techniques through literature research and field research by conducting interviews. To measure the effectiveness of law enforcement using an approach according to Soerjono Soekanto which is determined by 5 ( five ) factors, namely: the legal factor itself; law enforcement factors; facilities factors; societal factors, and cultural factors. The results of the study found that OSS in Bogor Regency has been implemented since 2018. Such is the case with the RBA OSS which can be implemented in August 2021. The regulations needed in the implementation of OSS in Bogor Regency were quite available, the Human Resources were competent, the facilities were adequate, the community was open to electronic services, and the community's digital literacy culture was quite good. Based on the evaluation of 5 (five ) factors that affect law enforcement, it can be concluded that OSS can be implemented effectively in Bogor Regency. Responding to the development of civilization globally and towards a golden Indonesia in 2045, OSS was a bridge process in realizing it all. The researcher suggested that the weaknesses and shortcomings in the RBA OSS should be immediately responded to by the Ministry of Investment / BKPM. The local government immediately prepares an internet network so that there are no blank spot areas, socialization is further intensified, and the required bylaws and regulations are immediately issued.